Refreshing Remodelling of the Classics - CÎNTEC, Oltița (Studia Universitatis Babeș-Bolyai Dramatica, 2023)
This paper deals with several reinterpretations and rewritings of classic texts by two directors, Susanne Kennedy and Silviu Purcărete. The theoretical framework is represented by Hans-Thies Lehmann’s idea of postdramatic theatre, but also by the reflection on how technological media change the way we look at classical texts. If Susanne Kennedy is passionate about Internet dramaturgy and technical devices, Silviu Purcărete, a director inspired by a visuality of pictorial origin, resorts to a more metaphorical-symbolic way of deconstructing the dramatic texts.